Use of Step-Section Histopathology to Evaluate F-Fluorocholine PET Sextant Localization of Prostate Cancer - Sandi A. Kwee; Gregory P. Thibault; Richard S. Stack; Marc N. Coel; Bungo Furusato; Isabell A. Sesterhenn (Molecular Imaging)
To assess positron emission tomography (PET) with fluorine-18 fluorocholine for sextant localization of malignant prostate tumors. Histopathologic analysis was performed on step-sectioned whole-mounted prostate specimens from 15 patients who underwent PET with fluorocholine prior to radical prostatectomy. The maximum standardized uptake value (SUVmax) corresponding to prostate sextants on PET was measured by region of interest analysis and compared with histopathologic results. Histopathology demonstrated malignant involvement in 61 of 90 prostate sextants. The mean total tumor volume per specimen was 4.9 mL (range 0.01–28.7 mL). Mean SUVmax was 6.0 ± 2.0 in malignant sextants and 3.8 ± 1.4 in benign sextants ( p < .0001). The area under the receiver operating characteristic curve was 0.82 for sextant detection of malignancy based on SUVmax measurement. Tumor diameter directly correlated with sextant SUVmax in malignant sextants ( r = .54, p < .05). In 13 subjects, the largest tumor in the specimen corresponded to the sextant with the highest SUVmax. Fluorocholine PET can serve to localize dominant areas of malignancy in patients with prostate cancer. However, PET with fluorocholine may fail to identify sextants with smaller volumes of malignancy.